2018
DOI: 10.1111/1756-185x.13257
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of asymptomatic vertebral fractures in inflammatory myositis

Abstract: Patients with inflammatory myositis have high prevalence of asymptomatic vertebral fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…20 In one study, low BMD increased the risk of subclinical fractures in patients with AIDS; 67% of HIV-infected patients had osteopenia and approximately 15% had osteoporosis. 21 The present study showed an increased risk of subclinical fractures in HIV-infected patients with a lower BMD of the third lumbar spine, consistent with the above findings. Numerous studies have shown that antiretroviral therapy is associated with bone loss and decreased BMD and consequent subclinical fractures.…”
Section: Discussionsupporting
confidence: 92%
“…20 In one study, low BMD increased the risk of subclinical fractures in patients with AIDS; 67% of HIV-infected patients had osteopenia and approximately 15% had osteoporosis. 21 The present study showed an increased risk of subclinical fractures in HIV-infected patients with a lower BMD of the third lumbar spine, consistent with the above findings. Numerous studies have shown that antiretroviral therapy is associated with bone loss and decreased BMD and consequent subclinical fractures.…”
Section: Discussionsupporting
confidence: 92%
“…The increased osteoporosis risk was independent of the corticosteroid and immunosuppressant treatments [9]. Gupta et al recently published a study about prevalence of vertebral deformities in patients with inflammatory myositis and found a high prevalence of asymptomatic vertebral fractures, but fracture risk and the consequences of fracture on physical function and quality of life were not examined [23]. Basically, fracture risk assessed without taking BMD into consideration showed a greater risk of fracture in patients with rheumatoid arthritis than in myositis patients.…”
Section: Discussionmentioning
confidence: 99%
“…The increased osteoporosis risk was independent of the corticosteroid and immunosuppressant treatments [9]. Gupta et al recently published a study about prevalence of vertebral deformities in patients with in ammatory myositis and found a high prevalence of asymptomatic vertebral fractures, but fracture risk and the consequences of fracture on physical function and quality of life were not examined [23]. Basically, fracture risk assessed without taking BMD into consideration showed a greater risk of fracture in patients with rheumatoid arthritis than in myositis patients.…”
Section: Discussionmentioning
confidence: 99%